Alleviating product inhibition of Trichoderma reesei cellulase complex with a product-activated mushroom endoglucanase. (January 2021) - Zou, Gen; Bao, Dapeng; Wang, Ying; Zhou, Sichi; Xiao, Meili; Yang, Zhanshan; Wang, Yinmei; Zhou, Zhihua
Graphical abstract: Highlights: The mushroom endoglucanase Pa Cel3A increases activity of T. reesei cellulase. The engineered mutant of Pa Cel3A improved thermostability. The viscometric CMCase activity was strongly promoted by 20 mM cellobiose. The saccharification rate of cellulase complex with Pa Cel3A increased by >50% Pa Cel3A relieves the product inhibition of T. reesei cellulase complex. Abstract: Product inhibition of cellulase is a challenging issue in industrial processes. Here, we introduced a product-activated mushroom cellulase, Pa Cel3A from Polyporus arcularius, into Trichoderma reesei . The filter paper activity, carboxymethyl cellulase activity, and saccharification efficiency (substrate: pretreated rice straw, PRS) of transformants increased significantly with this enzyme (by 18.4–26.8%, 13.8–22.8%, and 17.0%, respectively). A mutant of Pa Cel3A, Pa Cel3AM, obtained based on B-factor analysis, saturated mutagenesis, and residual activity assay, showed improved thermostability. The PRS saccharification efficiency using the cellulase complex from T. reesei transformants overexpressing pacel3am increased by 56.4%–63.0%. In addition, the T . reesei cellulase complex obtained by adding the purified recombinant Pa Cel3AM from T . reesei (rCel3aM-tr) to hydrolyze PRS resulted in increased reducing sugar yields at all sampling points, outperforming the cellulase complexes without rCel3aM-tr. These results suggest that introducing product-activated cellulase genes is a simple and feasible method to alleviate the product inhibition of cellulase.